Pengaruh Disiplin Kerja dan Budaya Organisasi terhadap Kinerja ASN pada Dinas Pemberdayaan Masyarakat dan Desa Provinsi Sumatera Barat - Doni Marlius; Andre Vebrian (JURNAL PUNDI, 2020)
Abstract              This research was conducted to prove the effect of work discipline and organizational culture on the performance of ASN in the Office of Community and Village Empowerment of West Sumatra Province. The Office of Community and Village Empowerment of West Sumatra Province was used as the population in this study. The sampling technique in which all members of the population are sampled is a total sampling of 49 samples. Data were collected using a questionnaire that was measured on a Likert scale. Furthermore, this study uses multiple linear regression analysis supported by the SPSS program. The results of the study indicate that work discipline influences the ASN performance, and organizational culture influences the ASN performance.Keywords       : Work Discipline, Organizational Culture, Performance